Foreign Cash: Taxes, Internal Capital Markets, and Agency Problems - Harford, Jarrad; Wang, Cong; Zhang, Kuo (Review of Financial Studies, 2017)
When the fraction of a firm’s cash held overseas is greater, its shareholders value that cash lower. This goes beyond a pure tax effect: the repatriation tax friction disrupts the firm’s internal capital market, distorting its investment policy. Firms underinvest domestically and overinvest abroad. Our findings are more pronounced when firms are subject to higher repatriation tax rates, higher costs of borrowing, and more agency problems. Overall, our evidence suggests that a combination of taxes, financing frictions, and agency problems leads to a valuation discount for foreign cash and documents real effects of how foreign earnings are taxed. Received January 19, 2015; editorial decision September 22, 2016 by Editor David Denis.